Phenotypic variation in oronasal perception and the relative effects of PROP and Thermal Taster Status - Yang, Qian; Hollowood, Tracey Ann; Hort, Joanne (Elsevier, 2014)
Individual variation in taste perception has long been investigated, particular in relation to PROP taster status (PTS). Recently, a new marker has been identified, Thermal Taster Status (TTS), whereby individuals are categorised as thermal tasters (TTs) or thermal non-tasters (TnTs) based on their ability to perceive taste solely from temperature stimulation. The aim of this study was to investigate the incidence of thermal tasters and relative effects of PTS and TTS on oronasal sensitivity across the whole perceptual range. Both detection thresholds (ASTM E679) and intensity measures at suprathreshold level (rated on gLMS) for stimuli from a range of modalities were determined from up to 124 subjects pre-screened for their PTS and TTS. No significant differences were found within either PTS or TTS groups at detection threshold level, with one exception; TTs has a lower threshold for sucrose (p<0.05). At supra-threshold level, PROP supertasters (pSTs) and medium tasters (pMTs) rated stimuli higher than non-tasters, and a consistent trend was observed that TTs rated stimuli higher than TnTs, although only ratings for temperature (warm and cold) reached significance. Global analyses applied across each modality, showed that in general TTs rated gustatory and trigeminal modalities significantly higher than TnTs, whilst this was not the case for olfactory stimuli, indicating that the mechanism for increased perception for TTs may be located in the oral cavity. PTS and TTS were shown to be independent phenotypes, but interestingly, ANOVA revealed significant interactions between TTS and PTS across the three modalities. Most notably, within pMTs, TTs rated stimuli intensity higher than TnTs, while the opposite trend was observed for pSTs. The intensity advantage gained by thermal tasters appears to be more apparent for pMTs than the already highly sensitive pSTs.